2019
DOI: 10.1177/0967033519872540
|View full text |Cite
|
Sign up to set email alerts
|

Near infrared spectroscopic measurement of strain in rocks

Abstract: The measurement of strain is a fundamental and widely studied parameter in engineering, rock mechanics, construction and materials testing. Contact sensors often used in these fields require contact with the target surface throughout the duration of a strain event. Non-contact methods typically require that that the measurement surface is prepared and often coated prior to testing. This paper considers the potential application of near infrared spectroscopy as a non-contact technique for the measurement of str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Axial force is monitored using a load cell and displacement (axial and radial) by linear variable differential transducer(s) (LVDT), strain gauge(s) glued onto the sample, optical/laser displacement transducer(s), and/or by a circumferential strain belt. A recent paper also found that near-infrared spectroscopy can be used as a non-contact technique for measuring strain (Butcher et al 2019). Force and displacement (corrected for the displacement of the loading chain) are then converted to axial stress and axial strain using the sample dimensions.…”
Section: Studying Mechanical Behaviour and Failure Mode In The Laboratorymentioning
confidence: 99%
“…Axial force is monitored using a load cell and displacement (axial and radial) by linear variable differential transducer(s) (LVDT), strain gauge(s) glued onto the sample, optical/laser displacement transducer(s), and/or by a circumferential strain belt. A recent paper also found that near-infrared spectroscopy can be used as a non-contact technique for measuring strain (Butcher et al 2019). Force and displacement (corrected for the displacement of the loading chain) are then converted to axial stress and axial strain using the sample dimensions.…”
Section: Studying Mechanical Behaviour and Failure Mode In The Laboratorymentioning
confidence: 99%